EKSISTENSI MAJELIS TAKLIM DALAM MEMBUMIKAN HADIS MELALUI ZIKIR - Junaid bin Junaid (IAIN BONE, 2019)
AbstractSocializing the Prophet's hadith through zikr includes the mu'tabar hadith and the Prophet's tradition which deal directly with the problem of zikr, the majority of which are used as a foundation in the taklim assembly, so it is clear that in Islam zikr has relevance that can create peace of mind for every Muslim in carrying out activities in daily life -day. In this case directly related to hablun min Allah and hablun min annas.Through Majelis Taklim as a forum for religious formation and personality which functions as a stabilizer in all movements of Muslim life activities, the hadith as the second source of law in Islam is very appropriate if the Islamic nuances receive attention and support from the community, so that the community has a balance of intellectual and mental-spiritual potential in an effort to deal with changing times from an increasingly global and advanced era.Keywords: Hadith; Majlis Taklim; Zikr.